Does Stock Market value Brands? - Eleftheriadou, Despoina (2007)
This dissertation tries to explore how the brand as an intangible asset impacts on the Market Value of the firm. Using a sample of 193 British firms and their Stock price of the year 2003, we tried to identify if the Stock Market value brands. According to the theoretical review and research results, each brand creates a different brand impact in consumer behaviour and in turn in Stock Market reaction. However, the Stock Market it seems that really values brand assets, firstly directly through the turnover and, secondly indirectly through the profit margin of the product